2022
DOI: 10.1155/2022/1416488
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of the Network Evolutionary Game Model of User Information Behavior on Enterprise Innovation Product Promotion Based on Mobile Social Network Marketing Perspective

Abstract: User information behavior is an important factor affecting the promotion effect of enterprises’ innovative products on mobile social networks. To provide insights as to how enterprises can better promote innovative products, this paper conducts a quantitative study of its internal function. We introduce a network evolutionary game model based on the Bass model, first to describe the background of the mobile social network, then to simulate the diffusion process of the social network and the user’s decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As an important driving force for enterprises' digital transformation, the government must give full play to the "promising government" effect. Relying on ABCD technology to promote government digital management, establish a professional information consulting platform, technical guidance platform, etc., to achieve efficient, active, precise, and flexible government governance, formulate a digital governance system that matches the digital economy, and give full play to the market role of resource optimization and allocation in digital transformation, creating a good external ecological environment for digital transformation and improving the efficiency of government digital services [29][30][31][32][33]. Strengthen the construction of infrastructure, optimize the industrial structure, form a digital development strategy, actively introduce relevant policies to provide technical support for the digital transformation of enterprises, and provide targeted financial support for the transformation of enterprises, so as to alleviate the financial difficulties faced by enterprises.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…As an important driving force for enterprises' digital transformation, the government must give full play to the "promising government" effect. Relying on ABCD technology to promote government digital management, establish a professional information consulting platform, technical guidance platform, etc., to achieve efficient, active, precise, and flexible government governance, formulate a digital governance system that matches the digital economy, and give full play to the market role of resource optimization and allocation in digital transformation, creating a good external ecological environment for digital transformation and improving the efficiency of government digital services [29][30][31][32][33]. Strengthen the construction of infrastructure, optimize the industrial structure, form a digital development strategy, actively introduce relevant policies to provide technical support for the digital transformation of enterprises, and provide targeted financial support for the transformation of enterprises, so as to alleviate the financial difficulties faced by enterprises.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In the Chinese financial system, banks play a dominant role in credit contracts, and the banks are regulated by the reform process of the banking industry. Government intervention will change the credit flow and scale of the banking industry [ 31 ]. As an important tool for the Chinese government to further deepen the reform and open up and advocate low-carbon green development, the BRI received strong support from governments at all levels.…”
Section: Literature Review Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Lee et al found that the potential agency costs of capital expenditure are arguably higher for high-free cash flow firms, and stronger monitoring by the board of directors can lead to higher level accounting conservatism thereby confirming the agency cost of cash flows hypothesis [ 34 , 35 ]. The BRI has resulted in a large amount of bank credit, government subsidies, tax incentives, and other policy resources to support energy-intensive enterprises [ 31 , 35 ]. Policy resources have resulted in energy-intensive companies generating large free cash flows.…”
Section: Literature Review Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…However, this complexity of information interweaving also presents challenges: once harmful information spreads within the network, it can cause significant damage. Beyond the challenges of information dissemination, social networks also play a crucial role in various fields such as healthcare [2,3], cultural education [4,5], and commercial marketing [6,7]. They are utilized for analyzing information, signals, and financial communication patterns, demonstrating their multifunctionality in modern society.…”
Section: Introductionmentioning
confidence: 99%